Akibat Hukum Pelanggaran Asas Pacta Sunt Servanda oleh Pembeli dalam Perjanjian Jual Beli Ditinjau dari Buku ke III KUHPerdata - Adittia Karyana; Sri Ratna Suminar (UNISBA Press, 2022)
This research identifies the problem of how the legal consequences if the buyer violates the principle of pacta sunt servanda in the sale and purchase agreement in terms of book III of the Civil Code. In addition, to examine how the legal protection for the seller if the buyer violates the principle of pacta sunt servanda in the sale and purchase agreement in terms of book III of the Civil Code JO Law Number 8 of 1999 concerning Consumer Protection. The purpose of this study is to examine and find out the legal consequences if the buyer violates the pacta sunt servanda principle in the sale and purchase agreement and forms of legal protection for the seller if the consumer violates the pacta sunt servanda principle which is based on the provisions of the Civil Code and Law Number 8 of 1999 concerning Consumer Protection. The method used in this research is a normative juridical approach through the use of secondary data. The normative approach is based on the use of statutory regulations as secondary data based on primary law as a primer material legal, and the other datas from secondary and tertiary legal materials. The results of the research is the legal consequences for buyers who violate the application of the principle of pacta sunt servanda is the need to provide compensation as stipulated in Article 1246 of the Civil Code. The legal protection of the seller in the sale and purchase agreement is guaranteed by the provisions of Article 1338 which contains the principle of pacta sunt servanda and is supported by the provisions of Article 6 of Law Number 8 of 1999 concerning Consumer Protection. Penelitian mengidentifikasi permasalahan tentang bagaimana akibat hukum apabila pembeli melanggar asas pacta sunt servandadalam perjanjian jual beli ditinjau dari buku III KUHPerdata. Selain itu juga untuk meneliti tentang bagaimana perlindungan hukum bagi penjual apabila pembeli melanggar asas pacta sunt servanda dalam perjanjian jual beli ditinjau dari buku III KUHPerdata JO Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. Tujuan penelitian ini guna mengkaji dan mengetahui akibat hukum apabila pembeli melanggar asas pacta sunt servanda dalam perjanjian jual beli dan bentuk perlindungan hukum terhadap penjual apabila konsumen melanggar asas pacta sunt servanda yang didasarkan pada ketentuan KUHPerdata dan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. Metode penelitian yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif melalui penggunaan data sekunder. Pendekatan normatif didasarkan kepada penggunaan peraturan perundang-undangan sebagai data sekunder berbahan hukum primer. Data sekunder lainnya diperoleh melalui pengumpulan bahan hukum sekunder dan tersier. Berdasarkan hasil penelitian akibat hukum terhadap pembeli yang melanggar penerapan asas pacta sunt servanda adalah perlunya memberikan ganti rugi sebagaimana diatur dalam Pasal 1246 KUHPerdata. Adapun perlindungan hukum terhadap penjual sebagai pelaku usaha dalam perjanjian jual beli dijamin oleh ketentuan Pasal 1338 yang mengandung asas pacta sunt servanda serta didukung melalui ketentuan Pasal 6 Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen.